PENGARUH BEBAN KERJA, DISIPLIN KERJA DAN KOMITMEN ORAGNISASI TERHADAP KINERJA PERANGKAT DESA BLIMBING, PANDAK, SUMBERSUKO KECAMATAN KLABANG BONDOWOSO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Assagaf, Mohammad Furkon; Praja, Yudha; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The aim of the research is to determine the influence of workload, work discipline and organizational commitment on the performance of Blimbing, Pandak, Sumbersuko village officials, Klabang Bondowoso District with Job Satisfaction as an Intervening Variable. The sampling technique used in this research was simple random sampling of 45 people. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that workload has a significant positive effect on job satisfaction, work discipline has a significant positive effect on job satisfaction, organizational commitment has a positive but not significant effect on job satisfaction, workload has a positive and significant effect on performance. , Work discipline has a negative but not significant effect on Performance, Organizational commitment has a positive but not significant effect on Performance, Job satisfaction has a positive and significant effect on Performance, Workload has a positive and significant effect on Performance through Job Satisfaction, Work discipline has a positive and significant effect on Performance village officials through job satisfaction, organizational commitment has a positive but not significant effect on performance through job satisfaction.